The protection of personal data in the spanish university libraries in the digital environment - Varela-Orol, Concha; Ameneiros Rodríguez, Rocío (Revista General de Información y Documentación, 2018)
The aim of this work is to analyse different aspects related to the protection of personal data in the websites of the libraries of the spanish public universities. Albeit with the inherent limitations of the research source, there are many weaknesses in the treatment of personal data in the digital environment that should be addressed in order to comply with the European Union's Data Protection Regulation. A number of actions are recommended for libraries, which affect both their own actions and the analysis of services provided by suppliers.
Keywords: Personal data protection; University libraries; Library confidentiality; Library privacy; Library identity management.